Метро 2033: Бездна: [фантастический роман] / Роберт Шмидт - Шмидт Роберт (Вселенная метро 2033, 2016)
Экземпляры: Ф. 7 (20240126) / Инвентарный номер: 45664 / Цена: 326.70 / Сис.шифр: Ш6(4Пол) / Авт.знак: Ш 733 / ГРНТИ: 17.82.31 / ББК: Ш6(4Пол)